Pendidikan Karakter dalam Surah al-Hujurat: Telaah Penafsiran Mahmud Yunus dalam Tafsir al-Karim - Mumtazah Al 'Ilmah; Salamah Noorhidayati; Ahmad Saddad; Siti Marpuah; Husnul Amira (Jurnal Semiotika Quran, 2023)
The Qur'an which was revealed in Arabic became a polemic on how the Qur'an could be understood and studied by people who could not speak Arabic. Then there appeared interpreters who aimed to make it easier to study the Qur'an to be practiced in daily activities. One of the most phenomenal and first works of interpretation in Indonesian is the Tafsir al-Karim which is a book written by Mahmud Yunus. This article aims to explore in depth how Mahmud Yunus interpreted in his Tafsir al-Karim, biography, style, method, and analysis of character education in the Tafsir al-Karim. The researcher concluded that there are 15 values ​​of character education in this Tafsir al-Karim, namely: politeness, birul walidain, respecting others, speaking well, being firm in one's stance, being fair, having good thoughts, tolerance, faith (tawhid), being humble, being pious, integrity, being grateful, being honest, and being responsible.